2020
DOI: 10.1038/s41598-020-57835-9
|View full text |Cite
|
Sign up to set email alerts
|

Mental health-related conversations on social media and crisis episodes: a time-series regression analysis

Abstract: We aimed to investigate whether daily fluctuations in mental health-relevant Twitter posts are associated with daily fluctuations in mental health crisis episodes. We conducted a primary and replicated time-series analysis of retrospectively collected data from twitter and two London mental healthcare providers. Daily numbers of 'crisis episodes' were defined as incident inpatient, home treatment team and crisis house referrals between 2010 and 2014. Higher volumes of depression and schizophrenia tweets were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Some recent investigations using NLP tools for psychiatric applications include predicting psychiatric readmission, 22 suicidality 23 , 24 or mental health crises 25 ; diagnosing mental illnesses 26 ; and predicting treatment outcomes in patients with depression. 27 These applications used a variety of NLP tools including rule-based systems (systems that use explicitly stated If/Then/Else rules), Artificial Neural Networks (ANN, models inspired by neurons that use weighted sums of inputs and activation functions), and deep neural networks (multi-layer ANN with each layer representing more advanced representation).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent investigations using NLP tools for psychiatric applications include predicting psychiatric readmission, 22 suicidality 23 , 24 or mental health crises 25 ; diagnosing mental illnesses 26 ; and predicting treatment outcomes in patients with depression. 27 These applications used a variety of NLP tools including rule-based systems (systems that use explicitly stated If/Then/Else rules), Artificial Neural Networks (ANN, models inspired by neurons that use weighted sums of inputs and activation functions), and deep neural networks (multi-layer ANN with each layer representing more advanced representation).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (e.g. Kolliakou et al, 2020;Pantic, 2014;Robinson et al, 2019) has shown that conversations on social media around mental health often provide spaces for anti-social behavior and the use of stigmatizing or demeaning language that could negatively affect the wellbeing of others, especially those most vulnerable users. A main finding of our analysis, however, is the overall positive discourse about mental health and related issues during MHAW 2017, as illustrated by the 884 tweets with a positive sentiment towards mental health.…”
Section: Main Findingsmentioning
confidence: 99%
“…From a public health perspective, the use of Twitter as a source of health information and guidance may be of special relevance [ 13 , 14 ]. This social media enables users to interact with a large number of people, sharing similar interests and concerns about their health and medical conditions [ 15 ]. Media outlets are considered to be sensors and drivers of society [ 16 ].…”
Section: Introductionmentioning
confidence: 99%